MEMAHAMI PENYEBAB KEBAKARAN HUTAN DAN LAHAN SERTA UPAYA PENANGGULANGANNYA: KASUS DI PROVINSI KALIMANTAN BARAT - PASARIBU, SAHAT M.; FRIYATNO, SUPENA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 1 Februari 2008)
Land and forest fire have grabbed much concern and been considered as national issue. The event occurs repeatedly year by year, specifically in Sumatra and Kalimantan islands. Government institutions and local community, including farmers and estate enterprises have a very close linkage in such disaster. The smoke produced by the fire has been transformed into a widespread of thick cloud and immediately affects health conditions of the community. The smoke also directly interfere river, land, and air transport systems, thus influencing basic socio-economic life of human being. This paper is aimed at understanding about how forest fire occurs and its effect on agricultural sector. With rapid rural appraisal method, this paper eventually comes to main results and findings as follows: (a) elaboration of five identified typologies of land and forest fire, (b) analysis of direct and indirect impacts of the fire on agricultural sector, (c) identification of who and why land and forest fire occur, and (d) recommendation of programs to persuasively eliminate land and forest fire. Many parties have its own share and proportion to contribute to land and forest fire. Imbalanced-nature occurs and causes specific disaster with environment degradation. People have many difficulties to recover from such situation. The successful to get rid of land and forest fire is heavily depending on how alternative applied technologies can easily be adopted and law enforcement can widely be implemented.
Keywords: Smoke, Peat Soil, Environment Degradation, Law Enforcement, Food and Estate Crops, Hot Spot